Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera: Ensifera: Stenopelmatoidea) XXII: New descriptions from Southwest China - Pang, Siyu; Zhang, Qianwen; Bian, Xun (Zootaxa, 2023)
In this paper, we report six new species and the female sex of four known species based on our new collections from Southwest China. All the specimens are deposited in Guangxi Normal University.